Edukasi Gizi dengan Media Audiovisual terhadap Pola Konsumsi Sayur Buah pada Remaja SMP di Jakarta Timur - Rike Minati Sekti; Adhila Fayasari (Sarana Ilmu Indonesia (salnesia), 2019)
Consumption of fruits and vegetables is one of the components in fulfilling balanced nutrition. Consumption of fruits and vegetables of the Indonesian population is still low, especially in school-age children or teenagers. This study aimed to analyze the effect of nutrition education with the normal lecturer and audiovisual media on knowledge and consumption pattern of fruit and vegetable of junior high school students. This research used a quasi-experimental design pretest-posttest one control group design in class VII SMPN 246 January-February 2017. Targets were selected through screening then selected who have an average of at least fruit and vegetable consumption. There were 2 groups in this study, lecture group and video combination lecture group, consisting of 36 subjects. Knowledge and consumption data of fruits were measured before and after the intervention. The intervention was carried out once and the post-test measurement 1 week after the intervention. Data analysis using t-test. Knowledge increases after getting education both in group lectures and video combination lectures. There was a significant increase in knowledge and consumption of fruits and vegetables after the intervention in the lecture group and the combination group. There was no difference in knowledge (p = 0,169), fruit consumption (p = 0,417) and vegetable consumption (p = 0,417) between students who were given nutrition education with lecture media and those who were given nutrition education with video combination lecture media.